A hero’s journey: the monomythical narrative of Diego Maradona’s World Cup appearances - Doehler, Steph (Funes. Journal of narratives and social sciences, 2022)
A genius and cultural figure who transcended the sport he played, Diego Maradona is one of the most important icons of popular football culture. The ‘Pibe de Oro’ attracted attention each time he graced the pitch, perhaps none more so than on the international stage at four World Cup tournaments between 1982-1994. Whilst social science research has failed to unequivocally define the notion of sports heroism, this paper aims to build upon this concept through the lens of a mythical narrative. We will trace Maradona’s World Cup appearances using Joseph Campbell’s narratological theory, the hero’s journey, through the monomyth template of three significant acts: the departure, the initiation and the return. This paper will provide a detailed enquiry into Maradona’s extraordinary skill and achievements, addressing both his World Cup highlights and lowlights for Argentina in an international journey that is unlikely to be replicated.